Genetic Analysis by nuSSR Markers of Silver Birch (Betula pendula Roth) Populations in Their Southern European Distribution Range - de Dato, Giovanbattista D.; Teani, Angela; Mattioni, Claudia; Aravanopoulos, Filippos; Avramidou, Evangelia V.; Stojnic, Srdjan; Ganopoulos, Ioannis; Belletti, Piero; Ducci, Fulvio (Frontiers in Plant Science, 2020)
In the main distribution area the genetic pattern of silver birch is dominated by two haplotypes: haplotype A located in the western and north-western Europe, and haplotype C in eastern and southeastern Europe, characterized by high levels of neutral genetic variability within populations, and low differentiation among populations. Information about the amount and structure of genetic variation in the southern marginal areas, representing rear populations left during the expansion of this species from southern glacial refugia, are lacking. The general aim of the study was to investigate the existence of the climatic characteristics typical of the environmental niche of the species, jointly to genetic organization, variation and gene flow, in marginal populations on the Italian Apennines and Greek Southern Rhodope and compare them with populations of the southern part of the main distribution range on the Alps and Balkans. Genetic analysis was performed using nuclear microsatellites loci on 311 trees sampled from 14 populations. Environmental analysis was performed on the multivariate analysis of derived climatic variables. The allelic pattern was analyzed to assess genetic diversity, population diversity and differentiation, population structure and gene flow. The geographic and environmental peripherality did not always match, with some Apennine sites at higher elevation enveloped in the environmental niche. In the peripheral populations on the Apennines, we observed a lower genetic diversity and higher differentiation, with evident genetic barriers detected around these sites. These characteristics were not shown in the marginal Greek populations. Unexpectedly, the southern Italian marginal populations showed genetic links with the Greek and central area of the distribution range. The Greek populations also showed evident gene flow with the Alpine and Balkan areas. The disparity of results in these two marginal areas show that it is not the geographic peripherality or even the ecological marginality that may shape the genetic diversity and structure of marginal populations, but primarily their position as part of the continuous range or as disjunct populations. This outcome suggests different considerations on how to manage their gene pools and the role that these rear populations can play in maintaining the biodiversity of this species.